The Formation Of Internationalization Strategies Within The Construction Industry:Vision and Strategy - Niittylä, Anna (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Internationalization represents a complex topic that has been researched for quite some time. However, since it continues to be extremely current a topic, its significance has not diminished, but maybe even increased in importance. Companies today face extreme pressure to enter new markets in the hope of growing, becoming more profitable, increasing market share, attracting new customers and meeting the requirements of its share- and stakeholders. In the increasingly global business environment of today, companies are facing both challenges and possible advantages of internationalization. Few companies are not operating internationally and it is becoming the question of ‘Why not?’ rather than ‘Why?’ to internationalize business operations. Internationalization and the importance of strategy are discussed in this research from the viewpoint of three case companies that were interviewed about internationalization strategies. This research project is a qualitative study that answers the research question of How is a business strategy constructed for entering a new market? The sub-questions are • How are goals set and what indicators are used to monitor the achievement of these goals? • What are the key characteristics of a strategy implementation process? The research method chosen for this study is a multiple-case study. Three case companies were chosen for the interviews in order to gain in-depth data of internationalization strategies within the construction industry.